The intellectual information system of medical aid control in the scope of Russian medical insurance; Journal of Physics: Conference Series; Vol. 803 : Information Technologies in Business and Industry (ITBI2016) - Taranik M. A. Maksim Alekseevich (2017, 2017)
Title screen